Coupling relationship between torch migration relative to surface weld pool and penetration morphology in asymmetrical fillet welding. (March 2019) - Yue, Jianfeng; Chang, Yushuo; Guo, Rui; Liu, Wenji; Li, Liangyu
Highlights: Close relation presents the torch migration and internal penetration deflection. Penetration deflection angle is smaller than welding angle for thermal inertia. Front image predicts penetration deflection to avert sidewall incomplete fusion. Penetration center angle can be predicted, and incomplete fusion can be evaluated. Abstract: Due to the asymmetry, on each side of the single-sided V-groove fillet weld of a plate steel, there is a certain gap between the heat conduction and heat dissipation. The thermal input is distributed randomly to both sides of the weld when unsuitable weld angle is applied during welding, and sidewall incomplete fusion defects of interior penetration often occurs. A new feasible methods is provided to predict the interior penetration morphology, preventing generation of incomplete fusion defects by acquiring the torch migration information of surface weld pool. The experimental results show that the torch migration relative to the surface of the weld pool occurs regularly when different welding angles are used. Meanwhile, the interior penetration morphology change. According to welding at different angles, the quantitative relation between them is established and verified by different welding current.